Sobre los tipos nomenclaturales de algunas especies linneanas de Teucrium, Phlomis y Thymus (Labiatae). About the nomenclatural types of some linnean species of Teucrium, Phlomis and Thymus (Labiatae) - López, Ginés; Morales, Ramón (Acta Botanica Malacitana, 2011)
Español. Se discute la tipificación y se propone modificar los tipos nomenclaturales aceptados en la actualidad de las especies linneanas Teucrium pseudochamaepitys, Teucrium polium, Phlomis lychnitis y Phlomis italica. Es necesario designar un iconótipo para la primera especie y se reivindican tipos anteriormente propuestos para las otras tres. Además se tipifica Thymus cephalotos, un nombre potencialmente problemático. English. The lectotypes of the Linnean species Teucrium pseudochamaepitys, Teucrium polium, Phlomis lychnitis and Phlomis italica currently accepted are discussed. We consider necessary to propose a lectotypus for the first species and to restore previously proposed ones for the other three. Also a lectotypus of Thymus cephalotos is proposed and the name considered to be a nomen ambiguum.